Understanding small and medium enterprises (smes) loan applications: comprehensive analysis from smes and loan providers - Mohd Ali, Mazurina; Haron, Noor Hasniza; Nik Abdullah, Nik Anis Idayu; Abdull Hamid, Nurhaiyyu (Research and Innovation Division, Universiti Teknologi MARA (UiTM) Selangor, 2025)
This comprehensive study investigates the financing landscape for small and medium enterprises (SMEs) from both the perspectives of loan providers and SMEs themselves. It employs a multifaceted approach to provide a holistic understanding of the factors influencing SMEs' financing decisions and shedding light on the crucial criteria that financial institutions consider when evaluating loan applications. This study utilized interviews with financial institutions to outline crucial loan approval criteria, emphasizing collateral, applicants’ characteristics, and business plans. Simultaneously, this study recognizes that financing remains a significant hurdle to the growth of SMEs which include the challenges, risks, and sustainability factors influencing SMEs' decisions in seeking external financing. Notably, it highlights challenges such as accounting knowledge and fluctuating demand, which expose SMEs to various risks like liquidity and technological risks, and subsequently explores sustainability concerns in the dynamic economic context of Malaysia, with the aim of bridging the information gap and empowering SMEs to enhance their financing prospects.